Legal Policy of Illegal Fishing Ship Sinking Policy in Protecting Marine Resources in Indonesia - Arlen Tyas Pangestu (JURNAL PENDIDIKAN IPS, 2025)
Indonesia's vast marine territory is seriously threatened by illegal fishing. The ship sinking policy based on Law No. 45/2009 on Fisheries is a firm step taken by the government to protect marine resources, marine ecosystems, and territorial sovereignty. This research uses a qualitative approach to examine the implementation of the policy as well as its environmental, legal and socio-economic impacts. The results show that this policy is effective in reducing illegal fishing and restoring marine ecosystems, especially coral reefs as an element of blue carbon. However, challenges such as diplomatic resistance, limited supervision, and environmental impacts require strategic solutions. Strengthened surveillance, optimal management of confiscated vessels, and international cooperation are needed for the sustainability of this policy.